Use of Calotropis procera to control Meloidogyne incognita race 2 in tomato - Costa, Natalia de Jesus Ferreira (2022)
The aim of this study was to investigate the potential of using Calotropis procera leaves in vitro and in vivo to control of Meloidogyne incognita race 2 in tomato (Solanum lycopersicum). In vitro tests consisted of evaluating the effect of the aqueous extract of leaves of C. procera (5 and 10%) on the hatching and mortality of juveniles of second stage considering the residence time of the J2 in the extract for 24 and 48 hours. In vivo tests consisted of evaluating the application of the extract to the soil and the incorporation of fresh leaves of C. procera (50 and 100 g/kg of soil) in pots with soil infested with M. incognita to control the nematode. After 48 hours, the 10% aqueous extract caused greater inhibition of hatching and mortality of J2. Results of in vivo tests demonstrated that the application of the aqueous extract to the infested soil caused a reduction in the number of galls, number of eggs masses, number of eggs and the reproduction factor of de M. incognita in tomato, and the incorporation of fresh leaves of C. procera into the soil promoted the eradication of M. incognita race 2.